1962
DOI: 10.1083/jcb.12.3.515
|View full text |Cite
|
Sign up to set email alerts
|

MACRONUCLEAR EVENTS IN SYNCHRONOUSLY DIVIDING TETRAHYMENA PYRIFORMIS

Abstract: The macronuclei of synchronously dividing mass cultures of Tetrahymena pyriformis (strain WH6) were examined with the electron microscope for changes during two division cycles. Samples were prepared at 30-minute intervals for a period of 81/~ hours which included the time required to induce synchrony by five heat shocks (41/~ hours). The interphase macronucleus contains peripheral, crescent-shaped nucleoli and evenly distributed chromatin bodies. Centrally located RNA bodies, composed of fibers, appear 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

1965
1965
1980
1980

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 14 publications
(17 reference statements)
3
20
1
Order By: Relevance
“…No nucleolar labelling was seen in 4 of these cells ( Figure 5), whereas 5 cells showed a 2 % to 5 % labelling of nucleoli ( Figure 7). A so-called RNA-body (8,23) was observed in 2 cells (20 %). The result of these observations was that 60 % of all cells showed some nucleolar labelling ( Figure 1…”
Section: Labelling During 60-70 Min Ehmentioning
confidence: 99%
“…No nucleolar labelling was seen in 4 of these cells ( Figure 5), whereas 5 cells showed a 2 % to 5 % labelling of nucleoli ( Figure 7). A so-called RNA-body (8,23) was observed in 2 cells (20 %). The result of these observations was that 60 % of all cells showed some nucleolar labelling ( Figure 1…”
Section: Labelling During 60-70 Min Ehmentioning
confidence: 99%
“…Elimination of nucleoli from the macronucleus during binary fission was reported in Paramecium bursaria (Ehret and Powers 1955) and Tetrahymena pyriformis (Elliott et at. 1962, Elliott 1963.…”
Section: Micronucleus In Late Anaphase Leaving a Long Tail Containinmentioning
confidence: 89%
“…Some of them, however, were on changes of the nucleoli rather than of the chromonemata (Ehret and Powers 1955, Roth and Minick 1961, Elliott et al 1962, Elliott 1963. Flickinger (1965) studied the morphology of the chromonemata throughout the cell cycle of Tetrahymena pyriformis, but he did not find any correlation between the morphological changes in the chromonemata and DNA synthesis.…”
mentioning
confidence: 99%
“…For many years, the study of dividing ciliates did not disclose the presence of discrete filaments in either the macro-or micronucleus (Roth, 1959;Roth and Minick, 1961;Elliot, ^ , 1962;Elliot, 1963); only the observations of Roth, and Roth and Minick indicated the possible presence of filaments associated with the amitotic macronuclear division.…”
Section: Filaments Of the Nuclear Apparatusmentioning
confidence: 99%
“…In an effort to answer these questions, a number of workers have expended considerable effort. Randall and Hopkins (1962) examined regenerating and dividing Stentor and embryonic chick trachea, Ehret and DeHaller (1963) extensively studied dividing Paramecium, and Sedar and Porter (1955), Roth (1960), Elliot (1962, and Roth and Shigenaka (1964) have examined different dividing ciliates; in no case was evidence found for the division of kinetosomes. Schuster (1963), in a study of the ameba-flagellate transformation of Naegleria, has observed structures that he suggests may be prekinetosomes developing in the apparent absence of formed kinetosomes.…”
Section: The Duplication Of Kinetosomes: Electron Microscopymentioning
confidence: 99%